Identify flows and power relations in Mozambique - Daniela de Brito (Abril, 2018)
By using the discussions around the concept of identity, this article intend to clarify, through the trajectory of the characters, how the novels Um rio chamado tempo, uma casa chamada terra, O outro pé da sereia, and, mainly, A varanda do frangipani, by Mia Couto, absorb and develop the identity issue, highlighting the coexistence among distinct groups and the author’s attempt to establish a more comprehensive approach to conflicts generated by the differences, established, generally, by interests of dominant groups.